Description Of Factors That Cause Breast Engorgement in Postpartum Women at TPMB Elis Lismayani Baregbeg Sub-District, Ciamis District - Rayi Tridesta Kharisma; Sri Heryani; Kurniati Devi Purnamasari (Journal of Midwifery and Public Health, 2025)
Breast engorgement is the damming of milk due to constriction of the lactiferous ducts or by incomplete emptying of the glands or due to nipple abnormalities. The breasts are hot and hard to the touch and painful; the body temperature does not rise. The nipples may be flat and this makes it difficult for the baby to suckle. Sometimes the release of breast milk is also blocked because the ductuli are narrowed due to enlarged veins and lymph vessels, the purpose of this study is to determine the description of what factors cause Breast Milk Damage (ASI) in Postpartum Mothers in Baregbeg sub-district, Ciamis district in 2024 which includes age, education, occupation, parity, gestational age, and knowledge. the research used is quantitative descriptive which aims to obtain a description of the factors that cause breast milk dams in postpartum mothers. The number of samples in this study consisted of 13 postpartum women respondents. The results of this study found that most respondents aged 20-25 years were 9 people (69.3%), had a junior high school education as many as 7 people (53.84%), the gestational age of the mother was aterem as many as 12 people (92.3), maternal peritas as many as 9 people (69.23%), maternal work as many as 10 people did not work (76.92%), and sufficient knowledge as many as 8 people (61.35).